2016
DOI: 10.1182/blood.v128.22.974.974
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Anti-CD19 Chimeric Antigen Receptor T Cells (CTL019) in Conjunction with Salvage Autologous Stem Cell Transplantation for Advanced Multiple Myeloma

Abstract: Background: Though CD19 is expressed only rarely on multiple myeloma (MM) plasma cells (PC), rare CD19+ B cells can be identified in MM patients that are clonally related to the MM PC. These clonotypic B cells may exhibit properties of cancer stem cells (enhanced MM-propagating properties and drug resistance compared to MM PC) and thus be a potential therapeutic target in conjunction with therapies that target MM PC. CTL019 consists of autologous T cells transduced via lentiviral vector with an anti-CD19 scFv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…To target this population, Garfall et al evaluated anti‐CD19 CAR T cells administered after salvage high‐dose melphalan + auto‐SCT in 10 relapsed/refractory MM patients who had previously exhibited early relapse (<12 months) after prior auto‐SCT. Two of 10 subjects exhibited longer response after salvage auto‐SCT + anti‐CD19 CAR T cells compared to their prior auto‐SCTs, suggesting benefit of CAR T cells in this subset . These two patients with prolonged responses also developed new immune responses against the stem‐cell antigen Sox2, suggesting immunogenic targeting of myeloma‐propagating cells.…”
Section: Cd19mentioning
confidence: 96%
“…To target this population, Garfall et al evaluated anti‐CD19 CAR T cells administered after salvage high‐dose melphalan + auto‐SCT in 10 relapsed/refractory MM patients who had previously exhibited early relapse (<12 months) after prior auto‐SCT. Two of 10 subjects exhibited longer response after salvage auto‐SCT + anti‐CD19 CAR T cells compared to their prior auto‐SCTs, suggesting benefit of CAR T cells in this subset . These two patients with prolonged responses also developed new immune responses against the stem‐cell antigen Sox2, suggesting immunogenic targeting of myeloma‐propagating cells.…”
Section: Cd19mentioning
confidence: 96%
“…The favorable side effect profile of this CAR‐T and the therapeutic rationale shows the potential of this target to be combined with other CAR‐T therapies and needs further testing in clinical trials. The safety and efficacy of combined infusion of CD19 and BCMA‐Specific CART cells is being tested in a clinical trial for relapsed/refractory myeloma (NCT 03196414) …”
Section: Chimeric Antigen Receptors: the Future Of Myelomamentioning
confidence: 99%
“…An update of this clinical trial on a series of 12 patients was reported at American Society of Hematology (ASH) meeting in December 2016. 70 Overall, 10 out of 12 patients enrolled were infused with CTL019 12-14 days after high-dose melphalan and an autograft. Six patients showed very good partial response (VGPR), 2 partial response (PR), 2 progressive disease (PD).…”
Section: Accepted Manuscriptmentioning
confidence: 99%